(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the science of world philology, the solution of scientific issues related to text creation in various genres, especially in the genres related to scientific research and educational pedagogy, as well as among the researches carried out in this regard, research on the study of the uniqueness of works related to text creation occupies an important place. However, the relevance of this issue is determined by the fact that this issue has not been studied in the field of scientific-creative texts, in particular, in the case of annotation, scientific review, abstract, term paper, and the conclusions of some scientific-theoretical researches related to the issue have not been generalized. Therefore, methodologically justifying the uniqueness of texts belonging to scientific genres in a modern style, researching in the methodological aspect of world and national philology science in a comparative plan are important and serious scientific issues that require comprehensive in-depth study.